Design And Development Of A Napier Grass Chopping Machine Based On A Rotary Blade Mechanism And Pull Roll System With A Capacity Of 1 Ton/Hour - Sayid Bahri Sriwijaya; Tika Kristianti; Ikbal Ikbal; Arya Kurniawan; Zikrillah Ferias (Journal of Innovative and Creativity, 2023)
The study purpose was to design, develop, and evaluate an elephant grass chopping machine that integrates a rotary blade mechanism and a pull roll system to improve feeding stability, productivity, and chopping uniformity in ruminant feed processing. Traditional manual chopping methods are labor-intensive, time-consuming, and produce inconsistent particle sizes, which reduce feed efficiency. This research aimed to develop a farm-scale machine with a target capacity of 1 ton/hour that is technically and economically feasible for farmers.Materials and methods. This study used an engineering-based research and development approach consisting of design, fabrication, and performance testing. The prototype was powered by a GX 220 gasoline engine and equipped with strip-type carbon steel rotary blades, a pull roll feeding system, and a pulley–V-belt transmission. Performance testing was conducted using elephant grass at three blade rotational speeds (1,120 rpm, 1,680 rpm, and 2,240 rpm). The observed parameters included chopping time, output mass, chopping capacity, and distribution of chopped sizes.Results. The machine achieved an optimal working capacity of approximately 1,080 kg/hour at a blade speed of 1,680 rpm, meeting the design target. Higher blade speeds reduced processing time and increased the proportion of smaller chopped particles, while lower speeds resulted in longer and less uniform cuts. The pull roll system effectively stabilized material feeding and enabled continuous operation.Conclusions. The developed machine improved labor efficiency, productivity, and feed chopping uniformity, indicating good potential for farm-scale application. However, further design improvements are required to reduce frame vibration, optimize hopper design, and enhance blade mounting safety.